Arginine and antioxidant supplement on performance in elderly male cyclists: a randomized controlled trial - Carpenter Catherine L; Henning Susanne M; Kim Woosong; Chen Steve; Li Zhaoping (Taylor & Francis Group, 2010)
Abstract Background Human exercise capacity declines with advancing age. These changes often result in loss of physical fitness and more rapid senescence. Nitric oxide (NO) has been implicated in improvement of exercise capacity through vascular smooth muscle relaxation in both coronary and skeletal muscle arteries, as well as via independent mechanisms. Antioxidants may prevent nitric oxide inactivation by oxygen free radicals. The purpose of this study was to investigate the effects of an L-arginine and antioxidant supplement on exercise performance in elderly male cyclists. Methods This was a two-arm prospectively randomized double-blinded and placebo-controlled trial. Sixteen male cyclists were randomized to receive either a proprietary supplement (Niteworks®, Herbalife International Inc., Century City, CA) or a placebo powder. Exercise parameters were assessed by maximal incremental exercise testing performed on a stationary cycle ergometer using breath-by-breath analysis at baseline, week one and week three. Results There was no difference between baseline exercise parameters. In the supplemented group, anaerobic threshold increased by 16.7% (2.38 ± 0.18 L/min, p < 0.01) at week 1, and the effect was sustained by week 3 with a 14.2% (2.33 ± 0.44 L/min, p < 0.01). In the control group, there was no change in anaerobic threshold at weeks 1 and 3 compared to baseline (1.88 ± 0.20 L/min at week 1, and 1.86 ± 0.21 L/min at week 3). The anaerobic threshold for the supplement groups was significantly higher than that of placebo group at week 1 and week 3. There were no significant changes noted in VO2 max between control and intervention groups at either week 1 or week 3 by comparison to baseline. Conclusion An arginine and antioxidant-containing supplement increased the anaerobic threshold at both week one and week three in elderly cyclists. No effect on VO2 max was observed. This study indicated a potential role of L-arginine and antioxidant supplementation in improving exercise performance in elderly.